Risk factors for methicillin-resistant Staphylococcus aureus colonization and infection in patients with human immunodeficiency virus infection: A systematic review and meta-analysis. Issue 1 (January 2022) - Hu, Xuefei; Hu, Keao; Liu, Yanling; Zeng, Lingbing; Hu, Niya; Chen, Xiaowen; Zhang, Wei
Objective: To investigate the potential factors affecting methicillin-resistant Staphylococcus aureus (MRSA) colonization and infection in patients with human immunodeficiency virus (HIV) infection. Methods: A systematic search of publications listed in electronic from inception up to August 2020 was conducted. A random-effects model was used to calculate odds ratio (OR) with 95% confidence interval (CI). Results: A total of 31 studies reporting 1410 MRSA events in 17 427 patients with HIV infection were included. Previous hospitalization (OR 1.80; 95% CI 1.37, 2.36), previous antibiotic therapy (OR 2.69; 95% CI 2.09, 3.45), CD4+ count (OR 1.79; 95% CI 1.41, 2.28), Centers for Disease Control and Prevention classification of stage C (OR 2.66; 95% CI 1.80, 3.93), skin lesions (OR 2.02; 95% CI 1.15, 3.55), intravenous device use (OR 2.61; 95% CI 1.59, 4.29) and an MRSA colonization history (OR 6.30; 95% CI 2.50, 15.90) were significantly associated with an increased risk of MRSA colonization and infection. Antiretroviral therapy (OR 0.71; 95% CI 0.50, 0.99) and current antibiotic use (OR 0.13; 95% CI 0.05, 0.32) were significantly associated with a reduced risk of MRSA colonization and infection. Conclusion: MRSA colonization and infection in HIV-infected patients is associated with a number of risk factors.